OUTDOOR THERMAL PERFORMANCE COMPARISON OF SEVERAL GLAZING TYPES - Rizki Fitria Madina (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2019)
ABSTRACTRecently, urban air temperature has been increasing, which can be attributed to the vast development, land cover changes, urban geometry, and surface material. Several strategies can be applied to mitigate the urban heat island intensity, one of which is the use of a cool and reflective material to avoid solar heat gain. In this study, we simulate a simplified model of the Asia-Afrika region in Bandung and conduct a comparative analysis to determine the thermal performance of glass in the outdoor thermal environment. The study results demonstrate that the shading coefficient value of glass has a negative correlation with the outdoor air temperature.Keywords: glass; shading coefficient; outdoor thermal environment